Human Sox4 facilitates the development of CXCL13-producing helper T cells in inflammatory environments - Hiroyuki Yoshitomi (Nature Portfolio, 2018)
At inflammatory sites, ectopic lymphoid-like structures (ELS) can be induced through the function of chemokine CXCL13 produced by CD4+ T cells. Here the authors show that a transcription factor, Sox4, induces the expression of CXCL13 in CD4 T cells in vitro, and is associated with ELS formation in patients with rheumatoid arthritis.